Effects of long‐term immobilisation on endomysium of the soleus muscle in humans. Issue 10 (24th August 2021) - Thot, Georgina K.; Berwanger, Carolin; Mulder, Edwin; Lee, Jessica K.; Lichterfeld, Yannick; Ganse, Bergita; Giakoumaki, Ifigeneia; Degens, Hans; Duran, Ibrahim; Schönau, Eckhard; Clemen, Christoph S.; Brachvogel, Bent; et al.
Abstract : New Findings: What is the central question of this study? While muscle fibre atrophy in response to immobilisation has been extensively examined, intramuscular connective tissue, particularly endomysium, has been largely neglected: does endomysium content of the soleus muscle increase during bed rest? What is the main finding and its importance? Absolute endomysium content did not change, and previous studies reporting an increase are explicable by muscle fibre atrophy. It must be expected that even a relative connective tissue accumulation will lead to an increase in muscle stiffness. Abstract: Muscle fibres atrophy during conditions of disuse. Whilst animal data suggest an increase in endomysium content with disuse, that information is not available for humans. We hypothesised that endomysium content increases during immobilisation. To test this hypothesis, biopsy samples of the soleus muscle obtained from 21 volunteers who underwent 60 days of bed rest were analysed using immunofluorescence‐labelled laminin γ‐1 to delineate individual muscle fibres as well as the endomysium space. The endomysium‐to‐fibre‐area ratio (EFAr, as a percentage) was assessed as a measure related to stiffness, and the endomysium‐to‐fibre‐number ratio (EFNr) was calculated to determine whether any increase in EFAr was absolute, or could be attributed to muscle fibre shrinkage. As expected, we found muscle fibre atrophy ( P = 0.0031) that amounted to shrinkage by 16.6% (SD 28.2%) on day 55 of bed rest. ENAr increased on day 55 of bed rest ( P < 0.001). However, when analysing EFNr, no effect of bed rest was found ( P = 0.62). These results demonstrate that an increase in EFAr is likely to be a direct effect of muscle fibre atrophy. Based on the assumption that the total number of muscle fibres remains unchanged during 55 days of bed rest, this implies that the absolute amount of connective tissue in the soleus muscle remained unchanged. The increased relative endomysium content, however, could be functionally related to an increase in muscle stiffness.